Does the Fed beat the foreign-exchange market? - Sweeney, R.J. (Journal of Banking & Finance, 2000)
This paper’s estimates and tests of Fed intervention profits are the first that explicitly adjust for foreign-exchange risk premia; failure to adjust may grossly affect estimated profits. Profits appear economically and statistically significant, whether risk premia are modeled as time-constant or as appreciation’s market beta depending on Fed intervention. The estimates are sensitive to the method of risk adjustment and to the periods used. Because a key variable, cumulative intervention, is I(1), test statistics may have non-standard distributions, a problem affecting past tests; this paper’s tests account for non-standard distributions. Possible explanations of these profits have mixed empirical support in the literature.